Effect of agrochemicals on endophytic fungi community associated with crops of organic and conventional soybean (Glycine max L. Merril) - Stuart, Andressa Katiski da Costa; Stuart, Rodrigo Makowiecky; Pimentel, Ida Chapaval (Agriculture and Natural Resources, 2018)
The use of agrochemicals in crops worldwide can have important impacts on the environment where they are used, including the rhizosphere. The effects were assessed of triflumuron and fenoxaprop-Pethyl on the fungal endophyte community associated with soybean in conventional and organic crops, at 55 d and 75 d after seed germination. Diversity, richness, and evenness decreased in the conventional crop. The number of genera of fungi isolated also decreased from 29 in organic soybean to 20 in conventional soybean. The occurrence of genera was evenly distributed in organic soybean. In conventional soybean, there was an increased frequency of some genera over others, revealing an ecological imbalance induced by the use of the tested pesticides.